Using a capillary ketone monitor as part of a self-management programme to prevent diabetic ketoacidosis among adults in Saudi Arabia: a feasibility randomised controlled trial - Alharbi, Muneera (2024)
Background: Diabetic ketoacidosis (DKA) remains a life-threatening complication arising after prolonged hyperglycaemic episodes, with possible fatal consequences. Despite the improvement in the management of DKA in hospital settings, DKA contributes to 54%–76% of deaths among all T1DM-related deaths for patients aged less than 30 years old. Around one-fifth of deaths occurred at home or on arrival at the hospital. The routine self-monitoring of blood glucose and ketone bodies play a significant role in the early detection and management of DKA. Thus, allowing patients with T1DM to self-manage their diabetes and associated ketonaemia prevents the development of DKA and any related complications. However, the Kingdom of Saudi Arabia (KSA) has no guidelines for the self-monitoring and management of ketone body elevation among patients with diabetes mellitus (DM).